2006
DOI: 10.1007/s00280-006-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-man phase I tolerability and pharmacokinetic study of the cyclin-dependent kinase-inhibitor AZD5438 in healthy male volunteers

Abstract: AZD5438 is a novel cyclin-dependent kinase inhibitor with preclinical pharmacodynamic (PD) activity against a range of human tumour xenografts. A first-in-man tolerability and pharmacokinetic (PK) study involving single ascending doses of AZD5438 was conducted in healthy male volunteers. Single oral doses ranging from 5 to 160 mg were studied in 23 subjects. Dose-limiting nausea and vomiting occurred at 160 mg in the absence of prophylactic anti-emetics. The maximum tolerated dose (the dose at which no dose li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Cyclin dependent kinases (CDKs) promote progression through the cell cycle. CDKs are positively regulated by cyclins and negatively by CDK inhibitors (p 15,16,18,19,21,27,57 ). Other kinases such as Aurora, Mps1 and Bub are also critical in chromosome segregation probably due to redundancy of CDKs in the cell and cyclin E may partner with another CDK target when CDK2 is not available [2,14].…”
Section: New Drug Development Targeting the Cell-cyclementioning
confidence: 99%
“…Cyclin dependent kinases (CDKs) promote progression through the cell cycle. CDKs are positively regulated by cyclins and negatively by CDK inhibitors (p 15,16,18,19,21,27,57 ). Other kinases such as Aurora, Mps1 and Bub are also critical in chromosome segregation probably due to redundancy of CDKs in the cell and cyclin E may partner with another CDK target when CDK2 is not available [2,14].…”
Section: New Drug Development Targeting the Cell-cyclementioning
confidence: 99%
“…In a phase i study in healthy volunteers, the drug was found to have a relatively short half-life of 1-3 hours 57,58 . Nevertheless, pd effects were demonstrated; the drug led to statistically significant reductions in the ratio phospho-pRb /total pRb detected at 1.5 hours post-dose, but the effect disappeared at 6 hours post-dose.…”
Section: Azd5438mentioning
confidence: 99%
“…Phase I clinical studies revealed a welltolerated agent at up to 80 mg administered as single oral doses. The dose-limiting adverse events were nausea and vomiting (49). A further, previously reported phase I clinical study, in which the pharmacodynamic activity of AZD5438 was evaluated (23), showed that the ratio of phospho-pRb/ total pRb was significantly reduced 1.5 hours after 40 and 80 mg AZD5438 compared with placebo.…”
mentioning
confidence: 99%
“…5 This model was adapted and combined with early human pharmacokinetic data (see ref. 49) to predict pRb response in buccal samples from healthy volunteers in the pharmacodynamic study described above (23). The closeness of the prediction from the model to the observed data suggested similarities in biomarker response to pRb between human xenograft cells implanted in nude mice and human buccal cells in healthy volunteers.…”
mentioning
confidence: 99%